Interfaith Marriage Between a Muslim Man and a Woman from People of the Book According to Article 40 C of the Compilation of Islamic Law (Analysis of Decision Number: 959/Pdt.P/2020/PN. Bdg., Dated. 2 December 2020 - Irvani, Firman Arief; Songgirin, Amin; Abubakar, Ibrahim (Indonesian Scientific Publication, 2023)
Interfaith marriage is a very sensitive issue to discuss. The debate over the rules for interfaith marriages is caused by differences in interpretation of the verses of the Koran which explain the laws of marriage. Scholars agree that the marriage of a Muslim woman to a non-Muslim man is invalid. Regarding the marriage of Muslim men to non-Muslim women, there are differences of opinion. If the woman is a Mushrik woman then the marriage is invalid, whereas if the woman is a People of the Book, there are still scholars who view the marriage as valid and there are also those who view it as invalid. With various considerations, both from the verses of the Koran, the hadith of the Prophet Muhammad, and the rules of fiqh, the Compilation of Islamic Law (KHI) as a guide for Religious Court judges to decide cases regarding matters of marriage, inheritance and waqf among Muslims has prohibited firmly and clearly the marriage of a Muslim man to a woman from the People of the Book and vice versa, the marriage of a Muslim woman to a man from the People of the Book. The result of this prohibition is that children resulting from interfaith marriages are classified as illegitimate children who do not have any relationship with their father and only have a civil relationship with their mother.